Volume 10: Ocean Renewable Energy 2017
DOI: 10.1115/omae2017-62040
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the Joint Industry Project Wave Impact on Fixed Foundations (WiFi JIP)

Abstract: The objective of the Joint Industry Project Wave impact on Fixed foundations (WiFi JIP) was to increase the understanding of breaking and steep wave impact’s on fixed foundations of offshore wind turbines (OWT). The project was set-up as a Joint Industry Project (JIP) and in total 20 companies and research institutes participated in the project. In this paper a summary of the complete WiFi JIP project will be presented. At the start of the project the state of the art design methods and guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This is because in tests 11 and 12, where waves are on average steeper than in tests 22 and 23, slamming loads from breaking waves are more frequent. The ESF method performs better than the WiFi model, which seems to provide conservative estimates, as also observed by de Ridder et al [23]. As for the 1000 year return storms, none of the models is clearly superior to the others.…”
Section: Comparisonsupporting
confidence: 69%
See 2 more Smart Citations
“…This is because in tests 11 and 12, where waves are on average steeper than in tests 22 and 23, slamming loads from breaking waves are more frequent. The ESF method performs better than the WiFi model, which seems to provide conservative estimates, as also observed by de Ridder et al [23]. As for the 1000 year return storms, none of the models is clearly superior to the others.…”
Section: Comparisonsupporting
confidence: 69%
“…We compare the DeRisk database methodology with the Embedded stream function (ESF) method from IEC-61400-1 [1], with the Wi-Fi JIP methodologies [23], and with linear and Second-Order irregular waves from Sharma and Dean [24].…”
Section: Ultimate Load States Computation: Current Approach Versus In...mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the moderately steep waves without the occurrence of wave breaking, the validity of the so-called Morison equation [4] has been investigated, primarily on slender piles [5,6,7,8]. A reasonable approximation of the wave loads using the Morison equation was achieved if correct wave kinematics were available in the context of wave modeling [7,9]. Paulsen et al [7] showed that, for moderately steep irregular waves, the Morison equation combined with a fully nonlinear two-dimensional potential flow solver was a good approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Although various wave breaking criteria have been developed and recommended by the offshore wind turbine loads standard [2], wave breaking in a realistic ocean environment has large variability in breaking wave conditions, which are typically determined by the site-specific conditions such as bathymetry, current and wind. The uncertainty is more pronounced regarding the wave loads and local stresses induced by the breaking waves as it involves the interaction of water, air and structural dynamics [9,14]. The total breaking wave loads are normally considered as an additional slamming force on top of the Morison force part in an engineering perspective.…”
Section: Introductionmentioning
confidence: 99%